Artificially and Sugar-Sweetened Carbonated Beverage Consumption Is Not Associated with Risk of Lymphoid Neoplasms in Older Men and Women. Issue 12 (23rd October 2014) - McCullough, Marjorie L; Teras, Lauren R; Shah, Roma; Diver, W Ryan; Gaudet, Mia M; Gapstur, Susan M
Abstract: Background: Concern about the carcinogenic potential of aspartame was raised after an increase in lymphomas and leukemia was reported in an animal study at doses similar to human exposure. Two prospective cohort studies published after the report found inconsistent results for estimated aspartame intake, artificially sweetened beverage consumption, and risk of lymphoid neoplasms. Objective: The objective of this study was to examine associations of artificially and sugar-sweetened carbonated beverage consumption (for comparison) and aspartame intake with risk of non-Hodgkin lymphoma (NHL) overall and by major histologic subtype in the Cancer Prevention Study-II Nutrition Cohort. Methods: Among 100, 442 adult men and women who provided information on diet and lifestyle factors in 1999, 1196 NHL cases were verified during a 10-y follow-up period. Cox proportional hazards regression was used to estimate multivariable-adjusted RRs and 95% CIs. Results: In women and men combined, there were no associations of consumption of ≥1 (355 mL) servings/d of artificially (RR: 0.92; 95% CI: 0.73, 1.17; P -trend: 0.14) or sugar- (RR: 1.10; 95% CI: 0.77, 1.58; P -trend: 0.62) sweetened carbonated beverages with NHL risk, compared to no consumption ( P -heterogeneity by gender: 0.11–1.00). Similarly, aspartame intake was not associated with NHL risk (RR: 1.02; 95% CI: 0.84, 1.24; P -trend: 0.69, top vs. bottom quintile). Associations with NHL subtype (multiple myeloma, diffuse large B-cell lymphoma, chronic lymphocytic leukemia/small lymphocytic lymphoma, and follicular and other B-cell lymphoma) were generally null. Conclusion: These findings do not support associations of daily consumption of artificially or sugar-sweetened carbonated beverages, or aspartame, with NHL risk.